2013
DOI: 10.1111/dote.12128
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative level of serum amyloid A is superior to C-reactive protein in the prognosis of esophageal squamous cell carcinoma

Abstract: Preoperative elevations in the levels of serum amyloid A (SAA) or C-reactive protein (CRP) have been reported to be prognostic indicators in several malignancies. The aim of this study is to evaluate the serum levels of SAA and CRP in the prognosis of esophageal squamous cell carcinoma (ESCC). In total, 252 patients with ESCC who had undergone surgery with curative-intent were retrospectively recruited. The specificity, sensitivity, and prognostic value of SAA or CRP levels were measured as the area under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Moreover, recent epidemiologic studies even suggest that elevated circulating levels of SAA, not only merely mark the presence of prevalent carcinoma, but also should possibly be related to an increased risk of future cancer in apparently healthy individuals (Sasazuki et al, 2010;Shiels et al, 2013). Most importantly, several researches have confirmed that SAA turned out to be an independent and effective factor in predicting survival of patients with different tumors (Kimura et al, 2001;Chan et al, 2007;Meng et al, 2014).…”
Section: Serum Amyloid a Is A Novel Prognostic Biomarker In Hepatocelmentioning
confidence: 99%
“…Moreover, recent epidemiologic studies even suggest that elevated circulating levels of SAA, not only merely mark the presence of prevalent carcinoma, but also should possibly be related to an increased risk of future cancer in apparently healthy individuals (Sasazuki et al, 2010;Shiels et al, 2013). Most importantly, several researches have confirmed that SAA turned out to be an independent and effective factor in predicting survival of patients with different tumors (Kimura et al, 2001;Chan et al, 2007;Meng et al, 2014).…”
Section: Serum Amyloid a Is A Novel Prognostic Biomarker In Hepatocelmentioning
confidence: 99%
“…A recent investigation demonstrated that SAA outperformed CRP in terms of prognostic accuracy for predicting 90-day mortality, overall survival and unfavorable outcomes in patients with intracerebral hemorrhage [ 34 ]. Similarly, a retrospective cohort study revealed that preoperative SAA levels exhibited superior predictive performance compared to CRP in determining overall survival among patients with esophageal squamous cell carcinoma [ 35 ]. These data suggests that SAA may serve as a more reliable prognostic indicator for various diseases, although our analysis did not reveal clear superiority of SAA over CRP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of tumor markers in early detection is severely limited because of their unsatisfactory sensitivities . Even TNM staging has limited roles in predicting survival, because outcomes may differ dramatically for patients within the same clinical stage . Thus, new biomarkers are required to predict patient survival and to select the patients who will benefit from specific treatments such as adjuvant therapies.…”
Section: Introductionmentioning
confidence: 99%